Acidifying surface water and water level management promote Sphagnum health for peatland restoration and paludiculture - Adam H.W. Koks; Sannimari A. Käärmelahti; Ralph J.M. Temmink; Alfons J.P. Smolders; Bas P. van de Riet; Leon P.M. Lamers; Roy C.J.H. Peters; Christian Fritz; Gijs van Dijk (Ecological Engineering, 2025)

The threat of groundwater pollution for petrifying springs; defining nutrient threshold values for an endangered bryophyte dominated habitat - Hans de Mars; Gijs van Dijk; Bas van der Weijden; Ab P. Grootjans; Lesław Wołejko; Gareth Farr; Jonathan Graham; Patrik Oosterlynck; Alfons J.P. Smolders (Environmental Pollution, 2024)

Determination of in vitro hepatotoxic potencies of a series of perfluoroalkyl substances (PFASs) based on gene expression changes in HepaRG liver cells - Jochem Louisse; Styliani Fragki; Deborah Rijkers; Aafke Janssen; Bas van Dijk; Liz Leenders; Martijn Staats; Bas Bokkers; Marco Zeilmaker; Aldert Piersma; Mirjam Luijten; Ron Hoogenboom; et al. (Archives of Toxicology, 2023)
Per- and polyfluoroalkyl substances (PFASs) are omnipresent and have been shown to induce a wide range of adverse health effects, including hepatotoxicity, developmental toxicity, and immunotoxicity. The aim of the present work was to assess whether human HepaRG liver cells can be used to obtain insight into differences in hepatotoxic potencies of a series of PFASs. Therefore, the effects of 18 PFASs on cellular triglyceride accumulation (AdipoRed assay) and gene expression (DNA microarray for PFOS and RT-qPCR for all 18 PFASs) were studied in HepaRG cells. BMDExpress analysis of the PFOS microarray data indicated that various cellular processes were affected at the gene expression level. From these data, ten genes were selected to assess the concentration–effect relationship of all 18 PFASs using RT-qPCR analysis. The AdipoRed data and the RT-qPCR data were used for the derivation of in vitro relative potencies using PROAST analysis. In vitro relative potency factors (RPFs) could be obtained for 8 PFASs (including index chemical PFOA) based on the AdipoRed data, whereas for the selected genes, in vitro RPFs could be obtained for 11–18 PFASs (including index chemical PFOA). For the readout OAT5 expression, in vitro RPFs were obtained for all PFASs. In vitro RPFs were found to correlate in general well with each other (Spearman correlation) except for the PPAR target genes ANGPTL4 and PDK4 . Comparison of in vitro RPFs with RPFs obtained from in vivo studies in rats indicate that best correlations (Spearman correlation) were obtained for in vitro RPFs based on OAT5 and CXCL10 expression changes and external in vivo RPFs. HFPO-TA was found to be the most potent PFAS tested, being around tenfold more potent than PFOA. Altogether, it may be concluded that the HepaRG model may provide relevant data to provide insight into which PFASs are relevant regarding their hepatotoxic effects and that it can be applied as a screening tool to prioritize other PFASs for further hazard and risk assessment.

Classical risk factors for primary coronary artery disease from an aging perspective through Mendelian Randomization - Swetta A. Jansen; Bas Huiskens; Stella Trompet; JWouter Jukema; Simon P. Mooijaart; Ko Willems van Dijk; Diana van Heemst; Raymond Noordam (GeroScience, 2022)

Biogeochemical Characteristics of the Last Floating Coastal Bog Remnant in Europe, the Sehestedt Bog - Gijs van Dijk; Christian Fritz; Nicko Straathof; Bas van de Riet; Niels Hogeweg; Sarah F. Harpenslager; Jan G. M. Roelofs; Karl-Ernst Behre; Leon P. M. Lamers (Wetlands, 2019)

Evaluation of the effectiveness of pre-employment screening - Bas Sorgdrager; Carel T. J. Hulshof; Frank J. H. van Dijk (International Archives of Occupational and Environmental Health, 2004)

Factors affecting FEV 1 in workers with potroom asthma after their removal from exposure - Bas Sorgdrager; Aart J. A. de Looff; Teake M. Pal; Frank J. H. van Dijk; Jan G. R. de Monchy (International Archives of Occupational and Environmental Health, 2000)